THE IMPORTANCE OF THE TRANSPORT SYSTEM IN THE REGIONAL INTEGRATION OF CENTRAL ASIA - No‘monxon Ibodulla o‘g‘li, Meliyev (ANTIS PUBLISHER, 2025)
Objective: This study examines the critical role of the transport system in fostering regional integration in Central Asia, a historically significant region with complex geopolitical and economic challenges. Method: The research employs a qualitative approach, utilizing a review of historical trade routes, policy analysis, and economic data to assess the impact of transportation infrastructure on regional connectivity. Results: Findings indicate that the development of transport systems has significantly enhanced trade, economic cooperation, and political stability among Central Asian nations. Improved infrastructure, such as railways, highways, and logistics hubs, has facilitated cross-border movement, reduced transaction costs, and strengthened economic ties with global markets. Novelty: Unlike previous studies that focus on individual country dynamics, this research provides a comprehensive regional perspective, highlighting how integrated transport networks serve as a catalyst for economic growth and geopolitical stability. The study underscores the need for sustainable and coordinated transport policies to maximize the benefits of regional integration in Central Asia.